Pitcairnia pseudoelliptica (Bromeliaceae) a new species from Junin, Peru - Gouda, Eric J. (Phytotaxa, 2025)
A new Pitcairnia species from Junin, Peru, P. pseudoelliptica is described, illustrated and compared to the morphologically closely related species P. elliptica from Ecuador and the wide spread P. rubiginosa from the Guianas and Amazonian Colombia, Venezuela, Peru and Brazil. This plant is in culture for many years at several botanical gardens in Europe and identified as P. elliptica, but is a distinct species.